PENGARUH PUPUK ANORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI HIJAU PADA TIGA JENIS TANAH - Dominggus.M.D. Tatuhey; Paskalius Apriyanto Merahabia; Herman Masbaitubun; Evi Tasriani; Grace Magdalena Wally (Jurnal Pertanian Terpadu Santo Thomas Aquinas, 2026)
Research The purpose of this study was to determine the appropriate fertilizer dosage and soil type to increase the growth and production of mustard greens. This study was conducted from October to November 2024. This study used a Randomized Block Design (RAK) consisting of 9 levels of fertilizer concentration. The research variables consisted of plant height, number of leaves, leaf length, leaf width and base weight. The results of the study showed significant differences in the plant height variable in the first week, second week, third week, fourth week, number of leaves in the first week, second week, third week, fourth week, leaf length in the fourth week, leaf width in the third week, fourth week and base weight variables. Of the 9 levels tested, the concentration with the highest results was the concentration of NPK fertilizer 300g + KNO3 300g + KCL 100g + Yahim Soil (C1).